Sibling relationships as a resource for coping with traumatic events - Perricone, Giovanna (Springer International Publishing, 2014)
The study investigated the correlation between the perception of sibling relationship to cope an adverse occurrence – the partial collapse of a primary school – and the indicators related to the traumatic impact set off by the event, by soliciting the child’s reminiscence of the catastrophic experience. One hundred trauma-exposed children were recruited from a Sicilian primary school and were administered the following research instruments: the Trauma Symptom Checklist for Children (TSCC-A), to investigate the traumatized response that can be triggered in the children involved; the Brother as a Resource Questionnaire (BRQ), to delve into the perception of sibling relationship as a resource. The outcomes showed statistically significant negative correlations between the Anxiety scale of the TSCC-A and the Scaffolding factors (r = −.260, p < .05) and Decision making process (r = −.315, p < 05) of the BRQ; between the Depression scale and the Scaffolding factors (r = −.147, p < .05), Emotional sharing (r = −.168, p < .05) and Decision making process (r = −.281, p < .05). The Anger scale correlated negatively with the Emotional sharing (r = −187, p < .05), the Decision making process (r = −.182, p < .05) and the Scaffolding factors (r = −.279, p < .05); the Post-traumatic Stress correlated negatively with the Scaffolding factors (r = −.203, p < .05) and the Decision making process (r = −.238, p < .05). Lastly, the Dissociation correlated negatively with the Decision making process (r = −.270, p < .05).